Factors associated with highly effective contraceptive use among reproductive-age women in Peru: Evidence from a nationwide survey. (February 2020) - Soriano-Moreno, David R.; Soriano-Moreno, Anderson N.; Mejia-Bustamante, Angela; Guerrero-Ramirez, Cristhian A.; Toro-Huamanchumo, Carlos J.
Abstract: Objective: This study aimed to assess the factors associated with highly effective contraceptive (HEC) use among reproductive-age women in Peru, using evidence from a nationwide survey. Study design: We analyzed the data corresponding to a national representative sample of 30, 169 Peruvian women aged 15–49 years, surveyed during the Demographic and Family Health Survey, 2017. Usage of HEC methods included pills, IUD, injections, sterilization and implant. We assessed the factors associated with its use using Poisson regression models, reporting the crude (cPR) and adjusted prevalence ratios (aPR) with their respective 95 % confidence intervals (95 % CI). Results: The prevalence of HEC use was 29.9 %. Factors related to a more likely use of HEC methods were having one (aPR: 4.03; 95 % CI: 3.19–5.09) or more children (aPR: 5.60; 95 % CI: 4.42–7.09), and having a health insurance children (aPR: 1.14; 95 % CI: 1.05–1.24). Women from the highlands (aPR: 0.74; 95 % CI: 0.67-0.81), aged ≥35 years (aPR: 0.78; 95 % CI: 0.67-0.90), not currently married or cohabiting (aPR: 0.52; 95 % CI: 0.47-0.58), and who considered it really hard to have to take transportation when they need medical help or advice (aPR: 0.92; 95 % CI: 0.86-0.99) were less likely to use highly effective contraception. Conclusion: Quality and access to reproductive health is still a challenge in Peru. Family planning programs should be better disseminated and integrated. Similarly, promotion of educational campaigns and easy access to HEC methods are needed.